Study on the characteristics of pipe buckling strength under pure bending and external stress using nonlinear finite element analysis - Hartono Yudo; Wilma Amiruddin; Ari Wibawa Budi Santosa; Ocid Mursid; Tri Admono (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2021)
Buckling and collapse are important failure modes for laying and operating conditions in a subsea position. The pipe will be subjected to various kinds of loads, i.e., bending moment, external pressure, and tension. Nonlinear finite element analysis was used to analyze the buckling strength of the pipe under pure bending and external pressure. The buckling of elastic and elasto-plastic materials was also studied in this work. The buckling strength due to external pressure had decreased and become constant on the long pipe when the length-to-diameter ratio (L/D) was increased. The non-dimensional parameter (β), which is proportionate to (D/t) (σy/E), is used to study the yielding influence on the buckling strength of pipe under combined bending and external pressure loading. The interaction curves of the buckling strength of pipe were obtained, with various the diameter-to-thickness ratio (D/t) under combination loads of external pressure and bending moment. For straight pipes L/D = 2.5 to 40, D = 1000 to 4000 mm, and D/t = 50 to 200 were set. The curved pipes D/t = 200, L/D =2.5 to 30 have been investigated by changing the radius of curvature-to-diameter ratio (R/D) from 50 to ∞, for each one. With decreasing R/D, the buckling strength under external pressure decreases slightly. This is in contrast to the bending of a curved pipe. When the value of R/D was decreased, the flexibility of the pipe was increased. However, the buckling strength of the pipe during bending was decreased due to the oval deformation at the cross-section.